2009
DOI: 10.1017/s1049096509990023
|View full text |Cite
|
Sign up to set email alerts
|

Trying to Thread the Needle: The Effects of Redistricting in a Georgia Congressional District

Abstract: In 2005 the Republican-controlled General Assembly redrew Georgia's congressional districts in order to gain additional seats in the 2006 midterm election. In this article we present a case study of the effects of redistricting on turnout and vote choice in Georgia's District 8 in the 2006 U.S. House election. It is apparent both from our findings and an elite interview, that unlike the more aggressive strategy employed by Texas Republicans in 2003, Georgia Republicans tried to thread the needle in their goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Much previous work has relied on imprecise measures of redrawn populations, such as the amount of overlap between a county and a congressional district, the district-level percentage of redrawn constituents, or changes in the districtlevel presidential vote (e.g., Abramowitz, Alexander, and Gunning 2006;Black and Black 2002;Gopoian and West 1984;Kousser 1996;McKee, Teigen, and Turgeon 2006;Petrocik and Desposato 1998;Swain, Borrelli, and Reed 1998;Winburn and Wagner 2010). But we join a growing number of studies that have been able to clearly differentiate between same-incumbent and redrawn voter populations with various units of aggregate-level data (see Ansolabehere, Snyder, and Hood and McKee 2009;Rush 1992Rush , 1993Rush , 2000. Likewise, our precinct-level data allow us to be confident that every precinct we refer to as "redrawn" has indeed been placed into a congressional district with a new incumbent.…”
Section: Datamentioning
confidence: 83%
See 1 more Smart Citation
“…Much previous work has relied on imprecise measures of redrawn populations, such as the amount of overlap between a county and a congressional district, the district-level percentage of redrawn constituents, or changes in the districtlevel presidential vote (e.g., Abramowitz, Alexander, and Gunning 2006;Black and Black 2002;Gopoian and West 1984;Kousser 1996;McKee, Teigen, and Turgeon 2006;Petrocik and Desposato 1998;Swain, Borrelli, and Reed 1998;Winburn and Wagner 2010). But we join a growing number of studies that have been able to clearly differentiate between same-incumbent and redrawn voter populations with various units of aggregate-level data (see Ansolabehere, Snyder, and Hood and McKee 2009;Rush 1992Rush , 1993Rush , 2000. Likewise, our precinct-level data allow us to be confident that every precinct we refer to as "redrawn" has indeed been placed into a congressional district with a new incumbent.…”
Section: Datamentioning
confidence: 83%
“…In a series of studies, we have found at the individual level a clear relationship between redistricting and a lack of familiarity with House incumbents, controlling for a host of potential confounds, such as education, partisanship, and other variables known to be associated with political awareness and participation (Hayes and McKee 2009;Hood and McKee 2009;McKee 2008). And critically, even in the presence of these controls, redistricting leads to higher rates of nonvoting in House elections (Hayes and McKee 2009).…”
Section: Addressing the Ecological Inference Problemmentioning
confidence: 91%
“…Most of this research, however, has focused on the elite‐level consequences of redistricting, considering questions of how redistricting affects who is elected. For example, studies have considered the effects of redistricting on incumbents’ reelection prospects (Desposato and Petrocik, ; Hood and McKee, ), partisan balance (Hood and McKee, ), the quality of voters’ representation (Yoshinaka and Murphy, ), and the policy representation of minority groups in Congress (Grose, ; Juenke and Preuhs, ), as well as contributing to the long‐running debate over the merits of race‐conscious redistricting as a vehicle for descriptive and substantive representation of minority interests, particularly among African Americans in the South (Overby and Cosgrove, ; Cameron, Epstein, and O'Halloran, ; Canon, ; Lublin, , ; Epstein and O'Halloran, ).…”
Section: Evidence Of Redistricting and Its Consequencesmentioning
confidence: 99%
“…In order of most to least important priority, Georgia Republicans wanted to smooth out the extant Democratic-drawn congressional boundaries, fortify a vulnerable Republican incumbent (Representative Phil Gingrey, GA-11), and unseat two Democratic Representatives-John Barrow and Jim Marshall (see Barone and Cohen 2007;Hood and McKee 2009). They accomplished the first two goals but failed to defeat Barrow and Marshall.…”
Section: Redistricting For the 2006 Midtermmentioning
confidence: 99%